Wheat (Triticum aestivum) crop response to irrigation scheduling and super absorbent polymers - SHWETA; SEWHAG, MEENA; MUNJAL, RENU; KUMARI, NISHA; MALIK, KAMLA; SAINI, ASHOK KUMAR; CHAUDHARY, KAUTILYA (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at research farm of CCS Haryana Agricultural University, Hisar, Haryana during winter (rabi) season 2018–19 and 2019–20 with an objective to study the polymers with irrigation effect on wheat (Triticum aestivum L.) crop. The research was done in a split-plot design with four irrigation [(No irrigation (I0), One irrigation at CRI stage, crown root initiation stage; (I1), Two irrigation at CRI, Booting (I2), Three irrigation at CRI, Booting, milking (I3)] and three polymer treatments [(No polymers (P0), Gondkatira @5 kg/ha (P1), Pusa Hydrogel @2.5 kg/ha (P2)] in the main and subplot respectively. The wheat seed yield decreased by 11.90% from I3 to I2, 17.12% from I3 to I1, and 33.74% from I3 to I0. The polymer treatment was used to increase the wheat seed yield. The yield was increased by 7.41% and 1.15% by application of hydrogel and gondkatira over no polymer. The minimum water productivity was registered under three irrigations. The application of gondkatira in wheat increased the water productivity by 8.09% while hydrogel 11.56%. Water stress or no irrigation has a lower Fv/Fm (Maximum quantum efficiency of PS II) (0.73) ratio than to no stress or three irrigations (0.75).